Bu Sabura é un Disgraça (International Library of African Music, 2015)
Audio example of traditional coladeira. Features Cape Verdean American musician Norberto Tavares playing his coladeira "Bu Sabura é un Disgraça.” Field recording by the author, Feb. 19, 1990.
Keywords: African Music